Conservation of a domestic metapopulation structured into related and partly admixed strains. Issue 7 (14th April 2018) - Ramljak, Jelena; Bunevski, Gjoko; Bytyqi, Hysen; Marković, Božidarka; Brka, Muhamed; Ivanković, Ante; Kume, Kristaq; Stojanović, Srđan; Nikolov, Vasil; Simčič, Mojca; Sölkner, Johann; Kunz, Elisabeth; et al.
Abstract: Preservation of genetic diversity is one of the most pressing challenges in the planetary boundaries concept. Within this context, we focused on genetic diversity in a native, unselected and highly admixed domesticated metapopulation. A set of 1, 828 individuals from 60 different cattle breeds was analysed using a medium density SNP chip. Among these breeds, 14 Buša strains formed a metapopulation represented by 350 individuals, while the remaining 46 breeds represented the global cattle population. Genetic analyses showed that the scarcely selected and less differentiated Buša metapopulation contributed a substantial proportion (52.6%) of the neutral allelic diversity to this global taurine population. Consequently, there is an urgent need for synchronized maintenance of this highly fragmented domestic metapopulation, which is distributed over several countries without sophisticated infrastructure and highly endangered by continuous replacement crossing as part of the global genetic homogenization process. This study collected and evaluated samples, data and genomewide information and developed genome‐assisted cross‐border conservation concepts. To detect and maintain genetic integrity of the metapopulation strains, we designed and applied a composite test that combines six metrics based on additive genetic relationships, a nearest neighbour graph and the distribution of semiprivate alleles. Each metric provides distinct information components about past admixture events and offers an objective and powerful tool for the detection of admixed outliers. The here developed conservation methods and presented experiences could easily be adapted to comparable conservation programmes of domesticated or other metapopulations bred and kept in captivity or under some other sort of human control.